2000
DOI: 10.1116/1.1319691
|View full text |Cite
|
Sign up to set email alerts
|

Influence of underlying interlevel dielectric films on extrusion formation in aluminum interconnects

Abstract: Effect of low-energy N 2 + ion beam bombardment on silicate glass thin films studied by x-ray photoelectron spectroscopy Knowledge of the mechanical properties of interlevel dielectric films and their impact on submicron interconnect reliability is becoming more and more important as critical dimensions in ultralarge scale integrated circuits are scaled down. For example, lateral aluminum ͑Al͒ extrusions into spaces between metal lines, which become more of a concern as the pitches shrink, appear to depend par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Several studies [18,19] have reported values of Young's modulus via measurement of the thermal stresses in thin films. More recent investigations have measured the elastic constants of silicon dioxide using methods such as nanoindentation [20] and atomic force microscopy [21]. However, none of these measurements are by tensile testing, which is the standard method for determining mechanical properties of structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [18,19] have reported values of Young's modulus via measurement of the thermal stresses in thin films. More recent investigations have measured the elastic constants of silicon dioxide using methods such as nanoindentation [20] and atomic force microscopy [21]. However, none of these measurements are by tensile testing, which is the standard method for determining mechanical properties of structural materials.…”
Section: Introductionmentioning
confidence: 99%
“…The refractive indices and stress levels of these films were very near those of doped silicon oxides deposited by conventional techniques. 13,19) …”
Section: Resultsmentioning
confidence: 96%
“…This is a compressive stress in the metal line because Al has a larger thermal expansion coefficient than both the dielectric and the substrate. As seen in published data [12], [13], the thermal stress depends on the aspect ratio of the line, the geometry of the interconnect structure, the mechanical properties of the dielectric and the temperature. Its magnitude can be more than 100 MPa.…”
Section: A Electromigration-induced Extrusion Failure Modementioning
confidence: 89%
“…As published data shows, low-k dielectrics have a lower fracture resistance compared to conventional dielectrics [3]. Metallization schemes using low-k materials as an interlayer dielectric (ILD) can cause a reliability problem because of an increased chance of cracking of the low-k dielectric due to a compressive stress induced by the EM driving force [4]. In these cases, use of design rules based solely on the open circuit failure mode could result in a less reliable product.…”
mentioning
confidence: 99%
See 1 more Smart Citation